The Nutrition Route following Esophagectomy - Abdelkader, Boukerrouche (International Journal of Nutrition, 2020)
Esophagectony remains a high-risk surgical procedure. Esophageal cancer is often associated with a weight loss. The best nutritional condition is crucial for successful oesophageal surgery. The increased septic complications and costs have limited the wide use of total parenteral nutrition. Currently, enteral nutrition is the preferred nutrition method following esophagectomy. However; jejunostomy-tube was associated with rare major complications that may lead to discontinuing nutrition. Choosing an enteral feeding route after esophagectomy depends greatly on the surgeon preference. The safety and benefits of early oral feeding on outcomes after major gastrointestinal surgery have been well documented. However, the surgical community is still reticent about initiating early oral feeding after esophageal surgery. Despite the limited number of published reports, comparative trials have clearly shown the feasibility, safety with no increase in morbidity rate.In this brief review, we tried to discuss the different routes of nutritional support after oesophagectomy with providing the current insights on early oral feeding.
Keywords: Esophagectomy; nutritional routes; parenteral nutrition; enteral nutrition; oral nutrition.